Toward a Pragmatist Sociology John Dewey and the Legacy of C. Wright Mills - Dunn, Robert G. (Temple University Press, 2018)
In Toward a Pragmatist Sociology, Robert Dunn explores the relationship between the ideas and principles of philosopher and educator John Dewey and sociologist C. Wright Mills to provide a philosophical and theoretical foundation for the development of a critical and public sociology. Dunn recovers an intellectual and conceptual framework for transforming sociology into a more substantive, comprehensive, and socially useful discipline.Arguing that Dewey and Mills shared a common vision of a relevant, critical, public sociology dedicated to the solution of societal problems, Toward a Pragmatist Sociology investigates the past and present state of the discipline, critiquing its dominant tendencies, and offering historical examples of alternatives to conventional sociological approaches. This original treatment of two influential American thinkers whose work offers a conception of and model for a sociology with public relevance and a sense of moral and political purpose should inspire future sociologists and others to regard the discipline as not only a science but also an intellectual, moral, and political enterprise.